6x - 3y = 36 x intercept: If y = 0, then 6x=36 so x=6 y intercept: If x = 0, then -3y=36 so y = -12
x=4 y=1 Therefore, 6x+5y=? Just substitute, and get 6*4+5*1=29
The solution is: x = 1 and y = -1
Add: 5x - y + x + y + 8 + 10 ie 6x = 18 so x = 3 and y = 7
It can be: y = 6x+4
(x, y) = (3, 7) is a solution.
x=1.5 and y=6x so y=6(1.5) y=9
x=3
y=9
x-y=6x=y+2Substitute y+2 for x in the 1st equation:(y+2) - y = 62=6Since this is false, there is no answer (the two lines are parallel)
x = 3/5 and y = 1/5
equation*6x-3*...answer*6(-4)-3=-27*...variable*x=-4*
24
y=6x² is already solved. the parabola will touch the x-axis at x=0.
10
y = x^2 - 6x + 11x + y = 2xx + y = 2xx - x + y = 2x - xy = xSubstitute x for y in the first equation:y = x^2 - 6x + 11x = x^2 - 6x + 11x - x = x^2 - 6x - x + 10 = x^2 - 7x + 11x = [-(-7) ± √[(-7)^2 - 4(1)(11)]]/(2)(1)x = (7 ± √5)/2x = (7 + √5)/2 or x = (7 - √5)/2x ≈ 4.618 or x ≈ 2.382Since y = x, then y ≈ 4.618 or y ≈ 2.382.Thus, we can say that the solution of the system are (2.382, 2.382) and (4.618, 4.618).
An equation with tw unknowns, x and y cannot be solved. Two different equations containing x and y and numbers (including 0 as a number). You have here Y = (X x 2) - 6X + 14, which equals 2X - 6X - 14 which equals (-4X) - 14, so Y = -(4X + 14), but you cannot find the values of X and of Y.